30-Day Journey with Dietrich Bonhoeffer - Mauldin, Joshua (30-Day Journey., 2019)
Enrich each day with wisdom from our greatest spiritual thinkers. Through brief daily readings and reflections, the 30-Day Journey series invites readers to be inspired and transformed. Known for his courageous resistance against Hitler, Dietrich BonhoefferÂs now-classic writings provide a powerful example of spiritual conviction. Whether you are familiar with Bonhoeffer or are encountering him for the first time, this journey provides the perfect way to engage with the thought of a pivotal Christian figure.